The effect of social media use towards consumers’ revisit intention to fast-food restaurant in Malaysia / Fairuz Abd Hakim, Irina Mohd Akhir and Suria Sulaiman - Abd Hakim, Fairuz; Mohd Akhir, Irina; Sulaiman, Suria (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The study examined the effect of social media use on consumers' revisit intentions to fast-food restaurants in Malaysia. Using the Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB), the study also explored the relationship between sociability, usability, dependence, and involvement in consumers' revisit intention. A survey was conducted using online questionnaires with 133 respondents using social media to search for fast food in Malaysia. Multiple linear regression analysis is applied to analyse the data in this study using SPSS. According to the findings, four aspects positively and negatively correlated with consumers' revisit intention. Involvement has the strongest relationship with consumers' revisit intention, whereas usability has the weakest. The findings are consistent with previous research, which found that involvement positively correlates with consumers' revisit intention to fast-food restaurants.